Assessment of post-fire vegetation recovery and soil erosion on slope containing nesosilicates - Nor Fatin Athirah, Nor Azman (2017)
Fires can reduce soil infiltration capacity induce soil water repellency and increase runoff and erosion. This study examines the effect of temperature under natural and laboratory condition of soil samples collected from hillside at Jalan Gambang. The unburned and burned soil samples were obtained from site. In addition, the soil samples under laboratory conditions were burned at three temperatures, which is 440ºC, 800ºC and 1350ºC. Various soil properties were studied, including specific gravity, Atterberg limits, swell index and organic matter content. The soil-water characteristic curve (SWCC) of all soil samples was also determined. The SWCC were established using chilled-mirror dew point technique and osmotic technique. Experiment results demonstrated that temperature at 440ºC, the liquid limit, organic matter content and SWCC were reduced and the swell index was eliminated. At 800ºC completely eliminated the liquid limit, plastic limit, swell potential and organic content of soil tested. The soil suction decreased with increasing temperature. From overall experimental results, the natural burned soil was predicted had experienced a fire at temperature below 440ºC. Furthermore, the removal of vegetation as affected by fire reduced the slope surface cover and caused erosion of the slope to occur. From the field work observation, the vegetation growths on natural burned soil are lesser compared to unburned soil. There are seven types of vegetation growth before the natural burned occurred but only six types of vegetation growth that are still growing even thought the amount is decreases.